2013
DOI: 10.5009/gnl.2013.7.3.278
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux Disease and Tooth Erosion: A Cross-Sectional Observational Study

Abstract: Background/AimsGastroesophageal reflux disease (GERD) is common in children. Recurrent exposure to gastric acid in GERD may contribute to tooth erosion.MethodsIn this prospective study, 54 GERD patients qualified according to endoscopy, pH-metry, and the GERD questionnaire and 58 healthy controls qualified by the GERD questionnaire were assessed. Two groups underwent dental evaluations for the presence, severity, and patterns of erosion and for the stage of dentition using a Tooth Wear Index. The health care p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 18 publications
3
37
0
6
Order By: Relevance
“…The association of dental erosion and GERD in our study is significant. Similar results were obtained by Fatemeh Farahmand et al [19], who found that 53 of 54 (98.1%) GERD patients and 11 of 58 (19.0%) controls had dental erosions (p<0.0001). Jarvinen et al [20] examined 109 patients with upper gastrointestinal symptoms and found only 6.4% to have erosion, while Meurman et al [21] found 26.2% out of 107 patients diagnosed with gastro-esophageal reflux to have dental erosion.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The association of dental erosion and GERD in our study is significant. Similar results were obtained by Fatemeh Farahmand et al [19], who found that 53 of 54 (98.1%) GERD patients and 11 of 58 (19.0%) controls had dental erosions (p<0.0001). Jarvinen et al [20] examined 109 patients with upper gastrointestinal symptoms and found only 6.4% to have erosion, while Meurman et al [21] found 26.2% out of 107 patients diagnosed with gastro-esophageal reflux to have dental erosion.…”
Section: Resultssupporting
confidence: 78%
“…Lower pH values in GERD patients according to other studies (19)(20)(21) confirm the higher risk of dental erosion in this condition.…”
Section: Resultssupporting
confidence: 60%
“…There is a positive correlation between GERD and DE and its presence in the primary dentition should be a key for the dentist to refer the child to the gastroenterologist [27]. The multidisciplinary approach facilitates the transmission of knowledge and widens the exchange of information between the different areas involved.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several structures can be damaged due to acid reflux, such as the pharynx, larynx, lungs, and the oral cavity, including the teeth. 7 The absence or delay of GERD treatment will lead to other serious complications, such as chronic inflammations of the gastric and esophageal mucosa, bleeding and serious blood loss, ulcers and concomitant functional disorders, difficulty in swallowing and narrowing of the esophagus. The upper airways can also be affected; asthma or pneumonia can be induced.…”
Section: Discussionmentioning
confidence: 99%